Intranasal delivery of Salmonella OMVs decorated with Chlamydia trachomatis antigens induces specific local and systemic immune responses - Dung T. Huynh; Emanuele Nolfi; Lobna Medfai; Peter van Ulsen; Wouter S. P. Jong; Alice J. A. M. Sijts; Joen Luirink (Human Vaccines & Immunotherapeutics)
Chlamydia trachomatis is an obligate intracellular pathogen responsible for the most prevalent bacterial sexually transmitted disease globally. The high prevalence of chlamydial infections underscores the urgent need for licensed and effective vaccines to prevent transmission in populations. Bacterial outer membrane vesicles (OMVs) have emerged as promising mucosal vaccine carriers due to their inherent adjuvant properties and the ability to display heterologous antigens. In this proof-of-concept study, we evaluated the immunogenicity of Salmonella OMVs decorated with C. trachomatis MOMP-derived CTH522 or HtrA antigens in mice. Following a prime-boost intranasal vaccination approach, two OMV-based C. trachomatis vaccines elicited significant humoral responses specific to the antigens in both systemic and vaginal compartments. Furthermore, we demonstrated strong antigen-specific IFN-γ and IL17a responses in splenocytes and cervical lymph node cells of vaccinated mice, indicating CD4+ Th1 and Th17 biased immune responses. Notably, the OMV-CTH522 vaccine also induced the production of spleen-derived CD8+ T cells expressing IFN-γ. In conclusion, these results highlight the potential of OMV-based C. trachomatis vaccines for successful use in future challenge studies and demonstrate the suitability of our modular OMV platform for intranasal vaccine applications.